2012
DOI: 10.4314/evj.v16i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Study on knowledge, attitude and dog ownership patterns related to rabies prevention and control in Addis Ababa, Ethiopia

Abstract: The study was conducted from May 2003 to August 2003 in Addis Ababa with the objective of understanding the distribution of stray and owned dogs, dog ownership patterns and attitudes of people towards rabies and its prevention and control methods. A total of 2390 households were selected from 6 Sub Cities of Addis Ababa using stratified random sampling and were interviewed using structured questionnaires. From the total households interviewed, 969 (40.5%) of them were known to own one or more dogs, and the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 3 publications
4
21
2
Order By: Relevance
“…In our study, 83.9%% people knew that the transmission was due to animal bite, which is more than the study done by Lai, et al 5 In their study, 61.1% transmission is by animal bite. In our study transmission by sneezing is 10.9%, which is similar to 12% as in Lai et al study.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…In our study, 83.9%% people knew that the transmission was due to animal bite, which is more than the study done by Lai, et al 5 In their study, 61.1% transmission is by animal bite. In our study transmission by sneezing is 10.9%, which is similar to 12% as in Lai et al study.…”
Section: Discussioncontrasting
confidence: 50%
“…Among the total females (66) about 83.3% said that rabies were transmitted by animal bite, 12.2% by sneezing and 3% does not know the exact mode of transmission and this relation between mode of transmission and sex is found to be statistically insignificant, whereas in a study by Lai P, et al 5 out of total males (98) 56.1% said that rabies was transmitted through animal bite, 9.2% by sneezing and 34.7% did not know about the transmission. Out of total females (28) 78.6% told animal bite, 10.7% sneezing and 10.7% did not know about mode of transmission and this relation was significant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In Swaziland, for instance, KAP surveys were used to investigate local communities' understanding of malaria transmission, recognition of symptoms, perceptions of causes, treatment-seeking patterns, and preventive measures and practices in order to provide baseline data for a national malaria control programme [20] . KAP surveys have also been applied to the study of rabies [17] , [21] [24] . However, before the research described herewith, no such studies had been conducted in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Ali Abraham et al reported 58.3% participants of the study had strong belief on traditional medicine, in Ethiopia [26]. Some consistence studies also reported all victims had attempted traditional medicine after exposure to bite, and they finally visited health centers when the traditional methods failed and clinical sings appeared [23,29]. Very high number of dog bite victims (90%) that received treatment by traditional healers in Bangladesh [30] was also other consistence report.…”
Section: Discussionmentioning
confidence: 92%